Supplementary Activities of The Capital Market School to Nurture The Spirit of Investment Consciousness - Nitawati, Elly Yuniar; Iman, Nurul; Sa’adah, Ummi; Putra, Briyan Cadalora (PT FORMOSA CENDEKIA GLOBAL, 2024)
Investment is the activity of putting a quantity of capital (money or other valuable assets) into an object, institution, or party with the hope that after a certain period of time it will make a profit. The term